2006
DOI: 10.1124/mol.105.018671
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the Phosphatidylinositol-3 Kinase/Protein Kinase B Signaling Pathway in the Neuroprotective Effect of Estradiol in the Striatum of 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine Mice

Abstract: The present experiments sought to determine the implication of estrogen receptors (ER␣ and ER␤) and their interaction with insulin-like growth factor receptor (IGF-IR) signaling pathways in neuroprotection by estradiol against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) toxicity. C57BL/6 male mice were pretreated for 5 days with 17␤-estradiol, an estrogen receptor ␣ (ER␣) agonist, 4,4Ј,4Љ-(4-propyl-[1H]-pyrazole-1,3,5-triyl)tris-phenol (PPT), or an estrogen receptor ␤ (ER␤) agonist, 5-androsten-3␤, 17␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 41 publications
3
68
0
1
Order By: Relevance
“…In this study, we found that E2 reduces the phosphorylation of β-catenin after GCI reperfusion in E2-treated FLOX control mice; however, in PELP1 FBKO mice, E2-mediated attenuation of β-catenin phosphorylation was abolished. These findings suggest that PELP1 scaffolding function is critical for formation of an ERα-PI3K-Akt-GSK3β-β-catenin multimolecular complex that leads to the activation of further downstream signaling (44,46). PELP1 FBKO mice also had a # P < 0.05 versus placebo; $ P < 0.05 versus FLOX placebo.…”
Section: Pelp1 Is Needed For Optimal Activation Of E2-regulated Genesmentioning
confidence: 88%
“…In this study, we found that E2 reduces the phosphorylation of β-catenin after GCI reperfusion in E2-treated FLOX control mice; however, in PELP1 FBKO mice, E2-mediated attenuation of β-catenin phosphorylation was abolished. These findings suggest that PELP1 scaffolding function is critical for formation of an ERα-PI3K-Akt-GSK3β-β-catenin multimolecular complex that leads to the activation of further downstream signaling (44,46). PELP1 FBKO mice also had a # P < 0.05 versus placebo; $ P < 0.05 versus FLOX placebo.…”
Section: Pelp1 Is Needed For Optimal Activation Of E2-regulated Genesmentioning
confidence: 88%
“…Several evidences have suggested that the neuroprotective effects of estrogen may be mediated by the activation of phosphatidylinositol-3 kinase (PI3K) signaling pathways and that ERα but not ERβ is involved of this intracellular signaling mechanism (Cardona-Gomez et al 2002a, 2002bMendez et al 2003;D'Astous et al 2006). The odds are that nonnuclear ERα is the isoform responsible of downstream activation of PI3K signaling pathway (Gundlah et al 2000).…”
Section: Nuclear Location Of Erα (Arrows) Citoplasmmatic Location Ofmentioning
confidence: 99%
“…Along these lines, a number of studies have demonstrated that estrogen is neuroprotective in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal lesions, an animal model of idiopathic PD [130][131][132][133][134][135][136][137][138][139][140]. Estrogen prevented MPTP-induced depletion of striatal dopamine, dopamine transporter binding and expression, decreased the MPTP-induced tyrosine hydroxylase-immunoreactive neuron loss and attenuated the glial activation induced by MPTP [130][131][132][133][134][135][136][137][138][139][140]. The estrogenic steroid principally used in these studies was 17β-estradiol (E2), and its effect on dopamine loss was shown by several studies to be stereospecific, as an isomer with weak estrogenic activity, 17α-estradiol, was ineffective at preventing MPTP-induced dopamine loss [131][132][133].…”
Section: Parkinson's Diseasementioning
confidence: 99%